Silicon Carbon Composite Particles

By depositing silicon in the pores of silicon-carbon composite particles and controlling its alkali metal or alkaline earth metal concentration and pH value, the problem of insufficient cycle stability of existing silicon-carbon composite particles is solved, and the high capacity efficiency and long life of lithium-ion batteries are achieved.

JP7662673B2Active Publication Date: 2025-04-15WACKER CHEMIE AG
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022578780
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-16
Publication Date
2025-04-15
Estimated Expiration
2041-04-16

AI Technical Summary

Technical Problem

The cycle stability of existing silicon-carbon composite particles is insufficient, especially in electric vehicle battery applications, resulting in the rapid reduction of the battery capacity of lithium-ion batteries after multiple charges and discharges.

Method used

By depositing silicon in the pores of the silicon-carbon composite particles, silicon-carbon composite particles with a concentration of 0.05-10 wt% alkali metal or alkaline earth metal and a pH value greater than 7.5 are formed.

Benefits of technology

It significantly improves the cycle stability of silicon-carbon composite particles, reduces the battery capacity attenuation of lithium-ion batteries, and improves the battery's high capacity efficiency and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662673000001
    Figure 0007662673000001
  • Figure 0007662673000002
    Figure 0007662673000002
  • Figure 0007662673000003
    Figure 0007662673000003
Patent Text Reader

Abstract

The subject of the present invention is a) silicon-carbon composite particles having an alkali metal or alkaline earth metal concentration of 0.05-10 wt % and b) a pH > 7.5; a method for producing said particles by infiltration of silicon from a silicon precursor in the presence of porous carbon particles; an anode material for lithium ion batteries comprising said silicon-carbon composite particles; an anode comprising a current collector coated with said anode material; and a lithium ion battery comprising at least one anode comprising said silicon-carbon composite particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silicon-carbon composite particles based on porous particles and silicon, a method for making the silicon-carbon composite particles, and their use as an active material in the anode for lithium-ion batteries. [Background technology]

[0002] As a storage medium for electrical power, the practical electrochemical energy storage device with the highest energy density is currently the lithium-ion battery. Lithium-ion batteries are mainly used in the field of portable electronics, for tools, and for motorized transport such as bicycles, scooters and automobiles. The currently popular material for the negative electrode ("anode") of such batteries is graphitic carbon. However, the disadvantage is that such graphitic carbon has a relatively low electrochemical capacity, theoretically at most 372 mAh per gram of graphite, which therefore corresponds to only about one tenth of the electrochemical capacity theoretically achievable with lithium metal. An alternative active material for the anode uses the addition of silicon, as described for example in EP 3335262 B1. Silicon forms an electrochemically active binary alloy with lithium, which allows a very high electrochemically achievable lithium content of up to 4200 mAh per gram of silicon.

[0003] The intercalation and deintercalation of lithium ions in silicon is associated with the disadvantage of being accompanied by a rapid change in volume, which can reach 300% in the case of complete intercalation. Such volume changes impose severe mechanical loads on silicon-containing active materials and can ultimately lead to their destruction. In active materials and electrode structures, this process, also called discharge polishing, leads to a loss of electrical contact and therefore a sustained and irreversible capacity loss on the part of the electrode.

[0004] Also, the surface of the silicon-containing active material reacts with the components of the electrolyte and continuously forms a passivating protective layer (solid electrolyte interface: SEI). The formed components are no longer electrochemically active. The lithium bound within them is no longer available to the system, resulting in a significant and continuous capacity loss on the part of the battery. Due to the extreme changes in silicon volume during charging and discharging of the battery, the SEI is periodically broken, which means that the not yet occupied surface of the silicon-containing active material is further exposed and then undergoes further SEI formation. In a full cell, the amount of mobile lithium corresponding to the available capacity is limited by the cathode material and is consequently gradually consumed, causing the capacity of the cell to drop to an unacceptable extent from the performance point of view after only a few cycles.

[0005] The decrease in capacity over the course of numerous charge-discharge cycles is also known as fading or continuous capacity loss, and is generally irreversible.

[0006] A series of silicon-carbon composite particles have been described for use as silicon-containing active material for the anode of lithium-ion batteries. In this case, the silicon-carbon composite particles are obtained, for example, starting from a gaseous or liquid silicon precursor, by pyrolysis of the latter, with the deposition of silicon in the porous carbon particles. For example, US 10,147,950 B2 describes the deposition of silicon from the monosilane SiH4 in porous carbon particles by the CVD ("chemical vapor deposition") or PE-CVD ("plasma enhanced chemical vapor deposition") method, at high temperatures of 300-900°C in a tube furnace or equivalent furnace type, preferably with stirring of the particles. Even in the composite materials obtained in this way, the cycle stability is not sufficient for use in demanding applications. Furthermore, the deposition of silicon requires high temperatures and / or long reaction times, which is very energy and time consuming.

[0007] Thus, a common feature of known silicon-carbon composite particles is that when they are used as active materials in anodes for lithium-ion batteries, they already exhibit low capacity loss in electrochemical cycles and therefore have good cycle stability as a result of low fading. However, for certain fields of application, particularly for use in batteries for electric vehicles, the achieved cycle stability is not sufficient and needs to be further improved.

[0008] Against this background, the objective is to provide silicon-carbon composite particles that, when used as active material in the anode of a lithium-ion battery, will undergo very little initial and ongoing loss of available lithium in the cell, thus enabling high coulombic efficiency and high cycling stability as a result of stable electrochemical behavior. It is desirable for this fading to be minimal.

[0009] This objective has surprisingly been achieved with silicon-carbon composite particles having a concentration of alkali metal or alkaline earth metal of 0.05-10 wt. % and a pH>7.5. When used as an active material for lithium-ion batteries, such silicon-carbon composite particles have a significantly increased cycling stability, which leads to a reduction in fading. Furthermore, it has surprisingly been found that in the production of silicon-carbon composite particles by deposition of silicon in porous carbon particles, starting from a gaseous or liquid silicon precursor, analogous to the above-mentioned CVD method, a significantly increased reaction rate can be observed when the porous carbon itself has a concentration of alkali metal or alkaline earth metal of more than 0.1-20 wt. % and a pH of more than 7.5.

[0010] The subject of the present invention is a) an alkali metal or alkaline earth metal concentration of 0.05 to 10 wt. %, and b) pH>7.5 The silicon-carbon composite particles have the following structure:

[0011] The porous carbon particles preferably have an alkali metal or alkaline earth metal concentration of 0.1 to 20 wt%, more preferably 0.2 to 10 wt%, and most preferably 0.3 to 5 wt%. The alkali metal and alkaline earth metal concentrations of the porous carbon particles can be quantitatively measured, for example, by ICP emission spectroscopy using a Perkin Elmer instrument "Optima 7300 DV".

[0012] The silicon-carbon composite particles of the present invention can be produced by any desired process.In particular, the production by depositing silicon from a gaseous or liquid silicon precursor into porous carbon particles by infiltration, similar to the process described in US10,147,950B2, is a suitable route for the silicon-carbon composite particles of the present invention.

[0013] Another subject of the invention is a method for producing the silicon-carbon composite particles of the invention by infiltration of silicon from a silicon precursor selected from liquid or gaseous silicon precursors at 20° C. and 1013 mbar in the presence of porous carbon particles having an alkali metal or alkaline earth metal concentration of 0.1 to 20 wt. % and a pH>7.5.

[0014] In this method, silicon is deposited within the pores and on the surfaces of porous carbon particles.

[0015] The deposition of silicon into the pores and on the surfaces of porous carbon particles by pyrolysis from a gas or liquid silicon precursor is referred to herein as silicon infiltration.

[0016] The same or different silicon precursors can be reacted with the same or different porous carbon particles.

[0017] By treating the porous carbon particles with a basic alkali metal compound or alkaline earth metal compound, porous carbon particles having an alkali metal or alkaline earth metal concentration of 0.1-20% and a pH>7.5 are obtained.

[0018] Preferred basic alkali metal or alkaline earth metal compounds are hydroxides, carbonates, hydrogen carbonates, percarbonates, amides, alkoxides, phenoxides, alkylates, hydrides, alkyds, silicates, disulfites, fluorides, cyanides, nitrites, peroxides, superoxides. Hydroxides, carbonates, hydrogen carbonates, percarbonates, hydrides, fluorides and amides are preferred, with hydroxides, carbonates, hydrogen carbonates, amides, hydrides, complex hydrides (tetrahydrometalates, e.g. BH4 or AlH4 with counterions, e.g. Li, Na, K, Mg, Ca, e.g. LiBH4, NaBH4, Li2Zn(BH4)4) being particularly preferred, and hydroxides, carbonates and hydrogen carbonates being especially preferred. The preferred basic alkali metal or alkaline earth metal compounds may be used alone or as a mixture of different basic alkali metal and / or alkaline earth metal compounds.

[0019] Porous carbon particles having an alkali metal or alkaline earth metal concentration of 0.1-20% and a pH>7.5 can alternatively be obtained by treating the porous carbon particles with a solution of a basic alkali metal or alkaline earth metal compound. The solvent used for the basic alkali metal or alkaline earth metal compound may be water, liquid ammonia, ketones such as acetone, alcohols such as ethanol, methanol, propanol, butanol, glycerol, hydrocarbons such as toluene, styrene, benzene, heterocyclic compounds such as pyridine and bipyridine, nitriles such as acetonitrile, sulfoxides such as dimethyl sulfoxide, and ethers such as tetrahydrofuran and 1,4-dioxane. Preferred solvents include water and alcohols such as ethanol, methanol, propanol and butanol, with particular preference being given to the use of water and ethanol, and most preferred to the use of water.

[0020] The porous carbon particles and the basic alkali metal or alkaline earth metal compound are used in a molar ratio of 100:1 to 5:1, more preferably 50:1 to 5:1, and most preferably 20:1 to 5:1, based on the carbon present in the form of carbon particles.

[0021] The porous carbon particles may be treated with the basic alkali or alkaline earth metal compound at a temperature below, above or at 20° C.; the treatment is preferably carried out at an elevated temperature. The temperature at which the porous carbon particles are treated with the basic alkali or alkaline earth metal compound is preferably from 30 to 200° C., more preferably from 50 to 160° C., and most preferably from 70 to 120° C.

[0022] The porous carbon particles may be treated with a basic alkali metal or alkaline earth metal compound under reduced pressure, atmospheric pressure or elevated pressure, preferably at atmospheric pressure or elevated pressure up to 5 bar, more preferably at atmospheric pressure.

[0023] The porous carbon particles may be treated with the solution of the basic alkali or alkaline earth metal compound in any desired reactor suitable for said treatment, more particularly by stirring a suspension of the porous carbon particles in the solution of the basic alkali or alkaline earth metal compound or by spraying the solution of the basic alkali or alkaline earth metal compound onto the porous carbon particles.

[0024] After the treatment of the porous carbon particles with the basic alkali metal or alkaline earth metal compound, the porous carbon particles are preferably released from the solution of the basic alkali metal or alkaline earth metal compound. This may be done, for example, by filtration or centrifugation; the treated porous carbon particles are optionally purified by water washing to remove excess basic alkali metal or alkaline earth metal compound. Alternatively, the treated porous carbon particles may be obtained by evaporating the solvent for the basic alkali metal or alkaline earth metal compound.

[0025] Prior to reaction with the gaseous or liquid silicon precursor, the porous carbon particles are preferably dried. Drying of the porous carbon particles may be carried out in any desired reactor suitable for drying, under an inert gas atmosphere, at an elevated temperature of 50-400°C. The inert gas used may be, for example, nitrogen or argon. Drying may alternatively be carried out at an elevated temperature of 50-400°C and a reduced pressure of 0.001-900 mbar. The drying time is preferably 0.1 seconds to 12 hours. The porous carbon particles may be dried in the same reactor as the reaction with the gaseous or liquid silicon precursor, or in a separate reactor suitable for drying.

[0026] The porous carbon particles have a density of 0.1-4 g / cm, as measured by helium pycnometry. 3 and preferably has a density of 0.3 to 3 g / cm 3 It is more preferred that the density of the granular material is 0.1 to 1.0 μm.

[0027] The porous carbon particles are classified into diameter percentiles d 50 Preferably, the diameter percentile d is 0.5 μm or more, more preferably 1.5 μm or more, and most preferably 2 μm or more. 50 is preferably 20 μm or less, more preferably 12 μm or less, and most preferably 8 μm or less.

[0028] The volume weighted particle size distribution of the porous carbon particles is preferably determined by the diameter percentile d 10≧0.2μm and d 90 ≦20.0 μm, more preferably d 10 ≧0.4μm and d 90 ≦15.0 μm, most preferably d 10 ≧0.6μm to d 90 ≦12.0 μm.

[0029] The porous carbon particles are classified into diameter percentiles d 10 Preferably, the diameter percentile d is 10 μm or less, more preferably 5 μm or less, particularly preferably 3 μm or less, and most preferably 2 μm or less. 10 is preferably 0.2 μm or more, more preferably 0.4 μm or more, and most preferably 0.6 μm or more.

[0030] The porous carbon particles are classified into diameter percentiles d 90 Preferably, the diameter percentile d is 4 μm or more, more preferably 8 μm or more. 90 is preferably 20 μm or less, more preferably 15 or less, and most preferably 12 μm or less.

[0031] The volume weighted particle size distribution of the porous carbon particles is preferably 15.0 μm or less, more preferably 12.0 μm or less, very preferably 10.0 μm or less, particularly preferably 8.0 μm or less, and most preferably 4.0 μm or less. 90 -d 10 The volume weighted particle size distribution of the porous carbon particles has a d span of preferably 0.6 μm or more, more preferably 0.7 μm or more, and most preferably 1.0 μm or more. 90 -d 10 It has a span.

[0032] Volume weighted particle size distributions can be measured by static laser scattering using the Mie model on a Horiba LA 950 instrument according to ISO 13320 using ethanol as the dispersion medium for the porous particles.

[0033] The porous carbon particles may, for example, be in isolated or agglomerated form. The porous carbon particles are preferably non-agglomerated and preferably non-agglomerated. Agglomerated generally means that in the manufacturing process of the porous carbon particles, primary particles are first formed and undergo fusion and / or the primary particles are linked to each other, for example via covalent bonds, thus forming aggregates. The primary particles are generally isolated particles. The aggregates or isolated particles can form agglomerates. Agglomerates are loose associations of aggregates or primary particles that are linked to each other, for example via van der Waals interactions or hydrogen bonds. Agglomerates in agglomerates can be easily broken back into agglomerates by conventional kneading and dispersion techniques. Agglomerates cannot be broken down into primary particles by these techniques or can only be broken down partially. The presence of the porous particles in the form of aggregates, agglomerates or isolated particles can be visualized, for example, by conventional scanning electron microscopy (SEM). Static light scattering methods for measuring particle size distribution or particle size of particles, in contrast, cannot distinguish between aggregates and agglomerates.

[0034] The porous particles may have any desired morphology and thus may be, for example, spheroid, platelet-like, spherical or acicular, with spheroid or spherical porous carbon particles being preferred.

[0035] The morphology can be characterized, for example, by the sphericity ψ or sphericity S. According to Wadell's definition, the sphericity ψ is the ratio of the surface area of ​​a sphere of equal volume to the actual surface area of ​​the object. For a sphere, the value of ψ is 1. According to this definition, the porous particles preferably have a sphericity ψ of 0.3 to 1.0, more preferably 0.5 to 1.0, and most preferably 0.65 to 1.0.

[0036] The sphericity S is the ratio of the circumference of an equivalent circle having the same area A as the projection of a particle onto a surface to the measured perimeter U of this projection.

[0037]

number

[0038] For particles with ideal circularity, the value of S is 1. For porous particles, the sphericity S is the percentile S of the number sphericity distribution. 10 ~S 90 Based on the above, the sphericity S is preferably in the range of 0.5 to 1.0, more preferably 0.65 to 1.0. The sphericity S is measured, for example, from optical micrographs of individual particles or, preferably, for particles <10 μm, using a scanning electron microscope and by graphic evaluation using image analysis software such as ImageJ.

[0039] The porous carbon particles are preferably 0.2 cm 3 / g or more, more preferably 0.6 cm 3 / g or more, most preferably 1.0 cm 3 / g or more, which is beneficial for obtaining lithium-ion batteries with high capacities. The gas-accessible pore volume is determined by gas adsorption measurements with nitrogen according to DIN 66134.

[0040] The porous carbon particles are preferably open-pore. Open-pore generally means that the pores are connected to the surface of the particle, for example through channels, and preferably allow the transfer of substances with the surroundings, in particular the exchange of gaseous components. This can be verified using gas sorption measurements (assessment according to Brunauer, Emmett and Teller, "BET"), i.e. the measurement of the specific surface area.

[0041] The porous carbon particles are preferably 50 mm 2 / g or more, more preferably 500m 2 / g or more, most preferably 1000m 2 / g. The BET surface area is determined in accordance with DIN 66131 (with nitrogen).

[0042] The pores of the porous carbon particles can have any desired diameter, i.e. usually in the range of macropores (>50 nm), mesopores (2-50 nm) and micropores (<2 nm). The porous carbon particles can be used in any mixture with different pore types. It is preferable to use porous carbon particles with at most 30% macropores relative to the total pore volume, more preferable to use porous carbon particles without macropores and very preferably to use porous carbon particles with at least 50% pores with an average pore diameter of less than 5 nm. More particularly preferably, the porous carbon particles contain only pores with a pore diameter of less than 2 nm (measurement method: pore size distribution in the mesopore range by BJH (gas adsorption) according to DIN 66134, in the micropore range by Horvath-Kawazoe (gas adsorption) according to DIN 66135; pore size distribution in the macropore range is evaluated by mercury porosimetry according to DIN ISO 15901-1).

[0043] The porous carbon particles preferably have a pH greater than 7.5, more preferably greater than 8.5, and most preferably greater than 9. The pH of the porous carbon particles can be measured by ASTM Standard No. D1512, Method A.

[0044] The porous carbon particles have an alkali metal or alkaline earth metal concentration of 0.05 to 10 wt %, preferably 0.1 to 5 wt %, and more preferably 0.15 to 2.5 wt %.

[0045] The silicon-carbon composite particles of the present invention have an alkali metal or alkaline earth metal concentration of 0.05 to 10 wt%, preferably 0.1 to 5 wt%, more preferably 0.15 to 2.5 wt%. The alkali metal concentration and alkaline earth metal concentration of the silicon-carbon composite particles of the present invention can be measured, for example, by ICP emission spectroscopy using a Perkin Elmer device "Optima 7300 DV".

[0046] The silicon-carbon composite particles of the present invention have a pH value greater than 7.5, preferably greater than 8.5, and most preferably greater than 9. The pH of the silicon-carbon composite particles of the present invention can be measured by ASTM Standard No. D1512, Method A.

[0047] The silicon-carbon composite particles of the present invention have a diameter percentile d 50 Preferably, the volume-weighted particle size distribution is in the range of 0.5 to 20 μm. 50 The value is 1.5 μm or more, more preferably 2 μm or more. Diameter percentile d 50 is preferably 13 μm or less, more preferably 8 μm or less.

[0048] The volume weighted particle size distribution of the silicon-carbon composite particles of the present invention is preferably determined by the diameter percentile d 10 ≧0.2μm and d 90 ≦20.0 μm, more preferably d 10 ≧0.4μm and d 90 ≦15.0 μm, most preferably d 10 ≧0.6μm to d 90 ≦12.0 μm.

[0049] The silicon-carbon composite particles of the present invention have a diameter percentile d 10 Preferably, the diameter percentile d is 10 μm or less, more preferably 5 μm or less, particularly preferably 3 μm or less, and most preferably 1 μm or less. 10 is preferably 0.2 μm or more, more preferably 0.4 μm or more, and most preferably 0.6 μm or more.

[0050] The silicon-carbon composite particles of the present invention have a diameter percentile d 90 Preferably, the diameter percentile d is 5 μm or more, more preferably 10 μm or more. 90 is preferably 20.0 μm or less, more preferably 15.0 μm or less, and most preferably 12.0 μm or less.

[0051] The volume-weighted particle size distribution of the silicon-carbon composite particles of the present invention is preferably 15.0 μm or less, particularly preferably 12.0 μm or less, more preferably 10.0 μm or less, particularly preferably 8.0 μm or less, and most preferably 4.0 μm or less. 90 -d 10 The silicon-carbon composite particles of the present invention preferably have a volume weighted particle size distribution of d of 0.6 μm or more, more preferably 0.7 μm or more, and most preferably 1.0 μm or more. 90 -d 10 It has a span.

[0052] The silicon-carbon composite particles of the present invention are preferably in the form of particles. The particles may be in the form of isolated or agglomerated. The silicon-carbon composite particles of the present invention are preferably non-agglomerated and preferably non-agglomerated. The terms isolated, agglomerated and non-agglomerated have already been defined above in relation to the porous carbon particles. The presence of the silicon-carbon composite particles of the present invention in the form of aggregates or agglomerates can be visualized, for example, by conventional scanning electron microscope (SEM).

[0053] The silicon-carbon composite particles of the present invention may have any desired morphology and thus may be, for example, spheroid, platelet-like, spherical or acicular, with spheroid or spherical particles being preferred.

[0054] According to Wadell's definition, sphericity ψ is the ratio of the surface area of ​​a sphere of equal volume to the actual surface area of ​​the object. For a sphere, the value of ψ is 1. According to this definition, the silicon-carbon composite particles of the present invention preferably have a sphericity ψ of 0.3 to 1.0, more preferably 0.5 to 1.0, and most preferably 0.65 to 1.0.

[0055] The sphericity S is the ratio of the circumference of an equivalent circle having the same area A as the projection of a particle onto a surface to the measured perimeter U of this projection.

[0056]

number

[0057] For particles with ideal circularity, the value of S is 1. For the silicon-carbon composite particles of the present invention, the sphericity S is the percentile S of the number sphericity distribution. 10 ~S 90 Based on the above, the sphericity S is preferably in the range of 0.5 to 1.0, more preferably 0.65 to 1.0. The sphericity S is measured, for example, from optical micrographs of individual particles or, preferably, for particles <10 μm, using a scanning electron microscope, by graphic evaluation, for example with image analysis software such as ImageJ.

[0058] The cycle stability of lithium ion batteries can be further improved through the morphology, material composition, particularly the specific surface area or internal porosity of the silicon-carbon composite particles of the present invention.

[0059] The silicon-carbon composite particles of the present invention preferably contain 10 to 90 wt. %, more preferably 20 to 80 wt. %, very preferably 30 to 60 wt. %, and especially preferably 40 to 50 wt. % silicon obtained by infiltration of the silicon-carbon composite particles of the present invention, based on the total weight of the silicon-carbon composite particles (preferably measured by elemental analysis such as ICP-OES).

[0060] The volume of silicon obtained by infiltration in the silicon-carbon composite particles of the present invention is calculated by multiplying the mass fraction of silicon obtained by infiltration from a silicon precursor as a percentage of the total mass of the silicon-carbon composite particles of the present invention by the density of silicon (2.336 g / cm 3 ) to obtain

[0061] The pore volume P of the silicon-carbon composite particles of the present invention is obtained by the sum of the gas-accessible pore volume and the gas-inaccessible pore volume. The gas-accessible pore volume according to Gurvich of the silicon-carbon composite particles of the present invention can be determined by gas sorption measurements with nitrogen according to DIN 66134.

[0062] The gas inaccessible pore volume of the silicon-carbon composite particles of the present invention can be determined by the following formula: Gas inaccessible pore volume = 1 / skeletal density - 1 / pure material density

[0063] The skeletal density in this specification is the density of a silicon-carbon composite measured by helium pycnometry in accordance with DIN 66137-2, and the pure material density of the silicon-carbon composite particles of the present invention is a theoretical density that can be calculated from the sum of the theoretical pure material densities of the components contained in the silicon-carbon composite particles of the present invention multiplied by their respective percentage ratios based on weight in the entire material. Thus, in the case of silicon-carbon composite particles: Pure material density = Theoretical pure material density of silicon (2.336 g / cm 3 ) × silicon ratio (wt%) + density of porous carbon particles (measured by helium pycnometry) × porous carbon particle ratio (wt%)

[0064] The pore volume P of the silicon-carbon composite particles of the present invention is preferably in the range of 0 to 400 vol.%, more preferably in the range of 100 to 350 vol.%, and very preferably in the range of 200 to 350 vol.%, based on the volume of silicon obtained by silicon infiltration and present in the silicon-carbon composite particles of the present invention.

[0065] The voids present in the silicon-carbon composite particles of the present invention may be gas-accessible or gas-inaccessible. The volume ratio of gas-accessible voids to gas-inaccessible voids in the silicon-carbon composite particles of the present invention may usually be in the range of 0 (no gas-accessible pores) to 1 (all pores are gas-accessible). The volume ratio of gas-accessible voids to gas-inaccessible voids in the silicon-carbon composite particles of the present invention is preferably in the range of 0 to 0.8, more preferably in the range of 0 to 0.3, and particularly preferably in the range of 0 to 0.1.

[0066] The pores of the silicon-carbon composite particles of the invention can have any desired diameter, for example located in the range of macropores (more than 50 nm), mesopores (2-50 nm) and micropores (less than 2 nm). The silicon-carbon composite particles of the invention may also comprise any desired mixture of different pore types. The silicon-carbon composite particles of the invention preferably comprise at most 30% macropores relative to the total pore volume, with silicon-carbon composite particles of the invention having no macropores being particularly preferred and silicon-carbon composite particles of the invention having at least 50% pores with an average pore diameter of less than 5 nm being very particularly preferred. More particularly preferably, the silicon-carbon composite particles of the invention comprise only pores with a diameter of at most 2 nm.

[0067] The silicon-carbon composite particles of the present invention preferably comprise silicon structures having a structure size in at least one dimension of preferably up to 1000 nm, more preferably less than 100 nm, very preferably less than 5 nm (measurement methods: scanning electron microscopy (SEM) and / or high-resolution transmission electron microscopy (HR-TEM)).

[0068] The silicon-carbon composite particles of the present invention preferably contain silicon layers in the pores and on the outer surface, with a layer thickness of at most 1000 nm, more preferably less than 100 nm, and very preferably less than 5 nm (measurement method: scanning electron microscopy (SEM) and / or high-resolution transmission electron microscopy (HR-TEM)). The silicon-carbon composite particles of the present invention may also contain silicon in the form of a layer formed from silicon particles. The silicon particles preferably have a diameter of at most 1000 nm, more preferably less than 100 nm, and very preferably less than 5 nm (measurement method: scanning electron microscopy (SEM) and / or high-resolution transmission electron microscopy (HR-TEM)). Note that the numerical value of the silicon particles here is preferably based on the diameter of the circle surrounding the particle in the microscopic image.

[0069] The silicon-carbon composite particles of the present invention have a maximum diameter of 100 mm. 2 / g, preferably 60m 2 / g, particularly preferably less than 20m2 The specific surface area is less than 1 / g. The BET surface area is measured according to DIN 66131 (using nitrogen). Therefore, when the silicon-carbon composite particles of the present invention are used as an active material in an anode for a lithium ion battery, it is possible to reduce the formation of SEI and improve the initial coulombic efficiency.

[0070] The silicon in the silicon-containing material deposited from the silicon precursor may further comprise a dopant selected from the group including, for example, Fe, Al, Cu, S, Cl, Zr, Ti, Pt, Ni, Cr, Sn, Ag, Co, Zn, B, P, Sb, Pb, Ge, Bi, rare earths or combinations thereof. In this specification, Li and / or Sn are preferred. The amount of dopant in the material comprising silicon-carbon composite particles is preferably up to 1 wt%, more preferably up to 100 ppm, based on the total weight of the silicon-carbon composite particles, and can be measured by ICP-OES.

[0071] The silicon-carbon composite particles of the present invention usually have a surprisingly high stability under compressive stress and / or shear stress.The pressure stability and shear stability of the silicon-carbon composite particles of the present invention are demonstrated herein, for example, by the fact that the silicon-carbon composite particles of the present invention show only slight or no change in their porous structure under compressive stress (e.g., during electrical compression) and shear stress (e.g., during electrode fabrication), respectively, in SEM.

[0072] The silicon-carbon composite particles of the present invention can be produced in any desired reactor that is commonly used for infiltration of silicon.Preferred reactors are selected from fluidized bed reactors, rotary tube furnaces, which can be oriented in any desired configuration from horizontal to vertical, and fixed bed reactors, which can be operated as open or closed systems, for example in the form of pressure reactors.Particularly preferred reactors are those that allow the porous particles and the silicon-containing material formed during infiltration to be mixed uniformly with the silicon precursor.This is advantageous for the extremely uniform deposition of silicon in the pores and on the surface of the porous particles.The most preferred reactors are fluidized bed reactors, rotary tube furnaces or pressure reactors, particularly fluidized bed reactors or pressure reactors.

[0073] Silicon is usually deposited by pyrolysis from silicon precursors. For silicon infiltration, it is possible to use one silicon precursor or a mixture or alternation of silicon precursors. Preferred silicon precursors are silicon hydrogen compounds such as monosilane SiH4, disilane Si2H6, and the higher linear, branched or cyclic homologs, neopentasilane Si5H. 12 , Cyclohexasilane Si6H 12chlorine-containing silanes, such as trichlorosilane HSiCl3, dichlorosilane H2SiCl2, chlorosilane H3SiCl, tetrachlorosilane SiCl4, hexachlorodisilane Si2Cl6 and higher linear, branched or cyclic homologues, such as 1,1,2,2-tetrachlorodisilane Cl2HSi-SiHCl2; chlorinated and partially chlorinated oligo- and polysilanes, methylchlorosilanes, such as trichloromethylsilane MeSiCl3, dichlorodimethylsilane Me2SiCl2, chlorotrimethylsilane Me3SiCl, tetramethylsilane Me4Si, dichloromethylsilane MeHSiCl2, chloromethylsilane MeH2SiCl, methylsilane MeH3Si, chlorodimethylsilane Me2HSiCl, dimethylsilane Me2H2Si, trimethylsilane Me3SiH, or mixtures of the mentioned silicon compounds. The silicon precursor is more particularly selected from monosilane SiH4, disilane Si2H6, chlorine-containing silanes, in particular trichlorosilane HSiCl3, dichlorosilane H2SiCl2, chlorosilane H3SiCl, tetrachlorosilane SiCl4, hexachlorodisilane Si2Cl6 and mixtures containing these silanes. Monosilane is particularly preferred.

[0074] In addition, one or more reactive components may be introduced into the reactor. Examples of such components are dopants based on compounds containing boron, nitrogen, phosphorus, arsenic, germanium, iron or nickel. The dopants are preferably selected from ammonia NH3, diborane B2H6, phosphine PH3, germane GeH4, arsine AsH3 and nickel tetracarbonyl Ni(CO)4.

[0075] Further examples of reactive components are hydrogen or hydrocarbons, more particularly aliphatic hydrocarbons having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, such as methane, ethane, propane, butane, pentane, isobutane, hexane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, etc.; ethylene, acetylene, propylene or butylene; unsaturated hydrocarbons having 1 to 10 carbon atoms, such as isoprene, butadiene, divinylbenzene, vinylacetylene, cyclohexadiene, cyclooctadiene, etc.; cyclic unsaturated hydrocarbons, such as cyclopropene, cyclobutene, cyclopentene, cyclohexene, cyclohexadiene, cyclopentadiene, dicyclopentadiene and norbornadiene; aromatic hydrocarbons, such as benzene, toluene, p-, m- and o-xylene, styrene (vinylbenzene), ethylbenzene, diphenylmethane and naphthalene; phenol, o-, m- and and further aromatic hydrocarbons such as p-cresol, cymene, nitrobenzene, chlorobenzene, pyridine, anthracene and phenanthrene, myrcene, geraniol, thioterpineol, norbornane, borneol, isoborneol, bornane, camphor, limonene, terpinene, pinene, pinane, carene, phenol, aniline, anisole, furan, furfural, furfuryl alcohol, hydroxymethylfurfural, bishydroxymethylfuran; as well as mixed fractions containing a plurality of such compounds, for example from natural gas condensates, petroleum distillates, coke oven condensates, mixed fractions from product streams from fluid catalytic crackers (FCC), steam crackers or Fischer-Tropsch synthesis plants, or, more generally, hydrocarbon-containing streams from the processing of wood, natural gas, petroleum and coal.

[0076] The process is preferably carried out in an inert gas atmosphere, such as, for example, a nitrogen or argon atmosphere.

[0077] In this process, the infiltration of silicon is preferably carried out at 280 to 900°C, more preferably 320 to 600°C, and particularly preferably 350 to 450°C.

[0078] The infiltration of silicon may be carried out under reduced pressure, atmospheric pressure or elevated pressure, the treatment being preferably carried out under atmospheric pressure or elevated pressure up to 50 bar.

[0079] Otherwise, the process can be carried out conventionally in a manner common to the infiltration of silicon from silicon precursors, with the usual modifications, if necessary, familiar to those skilled in the art.

[0080] A further subject of the present invention is an anode material for lithium-ion batteries comprising the silicon-carbon composite particles of the present invention.

[0081] The anode material is preferably based on a mixture comprising the silicon-carbon composite particles of the present invention, one or more binders, optionally graphite as further active material, optionally one or more further conductive components, and optionally one or more additives.

[0082] The anode material comprises silicon-carbon composite particles of the present invention, preferably one or more binders, optionally graphite as an additional active material, optionally one or more additional conductive components, and optionally one or more additives.

[0083] The use of a conductive component in the anode material can reduce the transmission resistance within the electrode and between the electrode and the current collector, thereby improving the current carrying capacity of the lithium ion battery. Preferred conductive components are conductive carbon black, carbon nanotubes, or metal particles, such as copper.

[0084] The primary particles of the conductive carbon black preferably have a diameter percentile d 10 = 5nm and d 90=200 nm. The primary particles of conductive carbon black can have chain-like branches and form structures up to μm in size. The carbon nanotubes preferably have a diameter of 0.4 to 200 nm, more preferably 2 to 100 nm, and most preferably 5 to 30 nm. The metal particles have a diameter percentile d 10 = 5nm and d 90 = 800 nm.

[0085] The anode material preferably comprises 0-95 wt %, more preferably 0-40 wt %, and most preferably 0-25 wt %, of one or more further conductive components, based on the total weight of the anode material.

[0086] The silicon-carbon composite particles of the present invention may be present in the lithium ion battery anode in an amount of preferably 5 to 100 wt %, more preferably 30 to 100 wt %, and most preferably 60 to 100 wt %, based on the total active material present in the anode material.

[0087] Preferred binders are polyacrylic acid or an alkali metal salt thereof, more particularly the lithium or sodium salt, polyvinyl alcohol, cellulose or a cellulose derivative, polyvinylidene fluoride, polytetrafluoroethylene, polyolefin, polyimide, particularly polyamideimide, or a thermoplastic elastomer, particularly an ethylene-propylene-diene terpolymer. Particularly preferred are polyacrylic acid, polymethacrylic acid, or a cellulose derivative, particularly carboxymethylcellulose. Particularly preferred are alkali metal salts of the above-mentioned binders, more particularly the lithium or sodium salt. Most preferred are alkali metal salts of polyacrylic acid or polymethacrylic acid, more particularly the lithium or sodium salt. All or preferably a part of the acidic groups in the binder may be present in the form of a salt. The binder preferably has a molar mass of 100,000 to 1,000,000 g / mol. A mixture of two or more binders can also be used.

[0088] The graphite used may typically be natural or synthetic graphite. The graphite particles preferably have a diameter percentile d 10 >0.2μm and d 90 Has a volume weighted particle size distribution of <200 μm.

[0089] Examples of additives include pore formers, dispersants, flow control agents or dopants, such as elemental lithium.

[0090] A preferred formulation of the anode material preferably comprises 5 to 95 wt%, more particularly 60 to 90 wt%, of the silicon-carbon composite particles of the invention; 0 to 90 wt%, more particularly 0 to 40 wt%, of a further conductive component; 0 to 90 wt%, more particularly 5 to 40 wt%, of graphite; 0 to 25 wt%, more particularly 5 to 20 wt%, of a binder; and optionally 0 to 80 wt%, more particularly 0.1 to 5 wt%, of further additives, the figures (wt%) being based on the total weight of the anode material and the percentages of all components of the anode material adding up to 100 wt%.

[0091] A further subject of the invention is an anode comprising a current collector coated with the anode material of the invention, said anode preferably being used in a lithium-ion battery.

[0092] The components of the anode material can be processed, for example, preferably using a rotor-stator machine, a high energy mill, a planetary kneader, an agitator ball mill, a shaker plate or an ultrasonic device, in a solvent preferably selected from the group comprising water, hexane, toluene, tetrahydrofuran, N-methylpyrrolidone, N-ethylpyrrolidone, acetone, ethyl acetate, dimethylsulfoxide, dimethylacetamide and ethanol, and mixtures of these solvents, to provide an anode ink or an anode paste.

[0093] The anode ink or anode paste preferably has a pH of 2 to 10 (measured, for example, at 20° C. using a pH meter WTW pH 340i with a SenTix RJD probe).

[0094] The anode ink or paste may be, for example, knife coated onto a copper foil or other current collector. Other coating methods, such as spin coating, roller coating, dip or slot die coating, painting or spraying, may also be used in the present invention.

[0095] Before the copper foil is coated with the anode material of the present invention, it may be treated with a commercially available primer, for example based on a polymeric resin or a silane, which can improve adhesion to the copper but which is usually not substantially electrochemically active itself.

[0096] The anode material is preferably dried to a constant weight. The drying temperature is guided by the components employed and the solvent used. It is preferably between 20°C and 300°C, more preferably between 50°C and 150°C.

[0097] The layer thickness, meaning the dry layer thickness, of the anode coating is preferably 2 μm to 500 μm, more preferably 10 μm to 300 μm.

[0098] Finally, the electrode coating may be calendered in order to establish a defined porosity. The electrodes thus produced preferably have a porosity of 15-85%, which can be measured by mercury porosimetry according to DIN ISO 15901-1. In this case, preferably 25-85% of the thus measurable pore volume is provided by pores with a pore diameter of 0.01-2 μm.

[0099] A further subject of the invention is a lithium-ion battery comprising at least one anode comprising the silicon-carbon composite particles of the invention, which may further comprise a cathode, two electrically conductive connections to the electrodes, a separator, an electrolyte impregnated in the separator and in the two electrodes, and may further comprise a housing containing the above-mentioned elements.

[0100] For the purposes of the present invention, the term "lithium ion battery" also encompasses a cell. A cell typically comprises a cathode, an anode, a separator and an electrolyte. Besides one or more cells, a lithium ion battery preferably further comprises a battery management system. The battery management system is typically responsible for controlling the battery by means of an electronic circuit, for example, in particular to recognize the charge state, to protect against exhaustion discharge or to protect against overcharging.

[0101] Preferred cathode materials employed are lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide (doped or undoped), lithium manganate (spinel), lithium nickel cobalt manganate, lithium nickel manganate, lithium iron phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium vanadium phosphate or lithium vanadate.

[0102] The separator is preferably an electrically insulating membrane, permeable to ions, made of polyolefins, such as polyethylene (PE) or polypropylene (PP), or polyesters, or corresponding laminates. As is customary in the manufacture of batteries, the separator may alternatively be made of glassy or ceramic materials or may be coated. As is known, the separator separates the first electrode from the second electrode, thus preventing an electronically conductive connection (short circuit) between the electrodes.

[0103] The electrolyte is preferably a solution containing one or more lithium salts (i.e. conductive salts) in an aprotic solvent. Preferred conductive salts are those selected from the group including lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium imide, lithium methide, LiCF3SO3, LiN(CF3SO2), and lithium borate. The concentration of the conductive salt is preferably from 0.5 mol / l to the solubility limit of the salt, based on the solvent. More preferably, it is 0.8 to 1.2 mol / l.

[0104] Examples of solvents which can be used are cyclic carbonates, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dimethoxyethane, diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, gamma-butyrolactone, dioxolane, acetonitrile, organic carbonates or nitriles, alone or in mixtures thereof.

[0105] The electrolyte preferably contains a film former, such as vinylene carbonate and fluoroethylene carbonate. In this way, a significant improvement in the cycle stability of the anode containing the silicon-containing material of the present invention can be achieved. This effect is mainly due to the formation of a solid electrolyte interface on the active particle surface. The proportion of the film former in the electrolyte is preferably 0.1 to 20.0 wt%, more preferably 0.2 to 15.0 wt%, and most preferably 0.5 to 10 wt%.

[0106] To achieve the highest mutual optimization of the real capacity of the electrodes of a lithium-ion cell, it is advantageous to quantitatively balance the materials for the positive and negative electrodes. Of particular importance in this context is the formation of an outer layer (known as formation) on the surface of the electrochemically active material in the anode during the first or initial charge-discharge cycles of a secondary lithium-ion cell. This outer layer is called the "solid electrolyte interface" (SEI) and generally consists, among other things, of electrolyte decomposition products and to some extent of lithium, which is therefore no longer available for further charge-discharge reactions. The thickness and composition of the SEI depend on the anode material used and on the nature and quality of the electrolyte solution used.

[0107] The SEI is particularly thin in the case of graphite, which typically results in a loss of 5% to 35% of the mobile lithium in the cell during the first charging step, with the reversible capacity of the battery being correspondingly reduced.

[0108] For anodes containing the silicon-carbon composite particles of the present invention, the loss of mobile lithium during the first charging step is preferably at most 30%, more preferably at most 20%, and most preferably at most 10%, which is well below the values ​​of the prior art, e.g., as described in US 10,147,950 B1 for silicon-containing composite anode materials.

[0109] The lithium ion batteries of the present invention can be manufactured in any conventional form, such as, for example, wound, folded, or stacked.

[0110] The materials and substances utilized in fabricating the lithium ion batteries of the present invention are all known, as discussed above, except for the silicon-carbon composite particles of the present invention. The components of the batteries of the present invention and their assembly to provide the batteries of the present invention are carried out according to techniques known in the art of battery manufacturing.

[0111] It is noted that the silicon-carbon composite particles of the present invention have significantly improved electrochemical behavior, leading to lithium-ion batteries with high volumetric capacity and excellent performance characteristics. The silicon-carbon composite particles of the present invention are permeable to lithium ions and electrons, allowing charge transport. The amount of SEI in lithium-ion batteries can be significantly reduced using the silicon-carbon composite particles of the present invention. Furthermore, due to the design of the silicon-carbon composite particles of the present invention, the SEI does not peel off from the surface of the silicon-carbon composite particles of the present invention, or at least peels off to a much lesser extent. All of this leads to higher cycling stability of the corresponding lithium-ion batteries. Fading and trapping can be minimized. Furthermore, the lithium-ion batteries of the present invention show little initial and ongoing loss of available lithium in the cell, and therefore show high coulombic efficiency.

[0112] In the following examples, all amounts and percentages are given by weight, all pressures are 0.10 MPa (absolute) and temperatures are 20° C., unless otherwise specified in each case. EXAMPLES

[0113] The pH value is measured according to ASTM Standard No. D1512, Method A.

[0114] Scanning Electron Microscopy (SEM / EDX): Microscopic observations were performed using a Zeiss Ultra 55 scanning electron microscope and an Oxford X-Max 80N energy dispersive X-ray spectrometer. To prevent charging phenomena, samples were vapor-coated with carbon using a Safematic 010 / HV compact coating unit prior to observation. Cross sections of silicon-containing materials were prepared using a Leica TIC 3X ion cutter at 6 kV.

[0115] Inorganic analysis / elemental analysis: The C content was determined using a Leco CS 230 analyzer, and the oxygen and nitrogen contents were determined using a Leco TCH-600 analyzer. Qualitative and quantitative determination of other elements, especially alkali and alkaline earth metals, was performed using ICP (inductively coupled plasma) optical emission spectrometry (Optima 7300 DV, Perkin Elmer). For this purpose, samples were acid digested (HF / HNO3) in a microwave oven (Microwave 3000, Anton Paar). The ICP-OES measurements were based on ISO 11885 "Water quality - Determination of selected elements by inductively coupled plasma optical emission spectrometry (ICP-OES) (ISO 11885:2007); German version EN ISO 11885:2009", which is used for the analysis of acidic aqueous solutions (e.g. acidified samples of drinking water, wastewater and other waters, aqua regia extracts from soils and sediments).

[0116] Particle size measurement: Particle size distribution was measured by static laser scattering with an LA 950 (Horiba) according to ISO 13320. In the preparation of the samples, particular attention should be paid to the dispersion of the particles in the measurement solution, in order not to measure the size of the aggregates rather than the individual particles. The materials observed here were dispersed in ethanol. Therefore, prior to the measurements, the dispersions were sonicated for 4 min with a laboratory ultrasonicator (Hielscher, model UIS250v, with LS24d5 sonotrode, 250 W), if necessary.

[0117] BET surface area measurement: The specific surface area of ​​the materials was measured by gas adsorption with nitrogen according to the BET method (measurement according to DIN ISO 9277:2003-05 with nitrogen) using a Sorptomatic 199090 instrument (Porotec) or a SA-9603MP instrument (Horiba).

[0118] Bone Density: The density of the framework, i.e. the density of the porous solid, which is based only on the volume of the pore space accessible to gas from the outside, was determined by helium pycnometry in accordance with DIN 66137-2.

[0119] Gas accessible pore volume (Gurvich pore volume): The gas-accessible pore volume according to Gurvich was determined by gas sorption measurements with nitrogen in accordance with DIN 66134.

[0120] In the following Invention Examples 1 to 6 and Comparative Example 1, the preparation and properties of the porous carbon particles used to prepare the silicon-carbon composite particles of the present invention are described.

[0121] Comparative Example 1: Porous carbon particles having an alkali / alkaline earth metal concentration <0.1 wt% and a pH <7.5 Porous carbon particles were used having the following characteristics: BET surface area: 2140m 2 / g Gurvich PV:1.01cm 3 / g Na content: 25ppm K content: 115ppm pH=5.4

[0122] Inventive Example 1: Treatment of Porous Carbon Particles with 1 Molar NaOH Solution A 250 ml flask was charged with 20 g of carbon from Comparative Example 1 and mixed with 160 ml of 1 M NaOH (aq) at room temperature. The suspension was then heated to 100° C. and boiled at reflux for 3 hours. After cooling to ambient temperature, the suspension was filtered through a suction filter and the solid product was washed with distilled water until the pH of the wash water was 7. The powder obtained was finally dried in a vacuum drying cabinet at 80° C. and 10 -2 The mixture was dried at 400 bar overnight, yielding 19.6 g of a black solid.

[0123] Example 2: Treatment of porous carbon particles with 1 Molar NaOH solution, followed by a washing step After treating the porous carbon particles in the same manner as in Example 1, the sample was further washed with 2 L of distilled water. The obtained powder was finally heated at 80° C. for 10 -2 The mixture was dried overnight in a vacuum drying cabinet at 100 bar, yielding 19.4 g of a black solid.

[0124] Inventive Example 3: Treatment of porous carbon particles with 1 Molar NaOH solution at room temperature A 250 ml flask was charged with 20 g of carbon from Comparative Example 1 and mixed with 160 ml of 1M NaOH (aq) at room temperature. The suspension was then stirred at room temperature for 1 hour, after which it was filtered through a suction filter and the solid product was washed with distilled water until the pH of the wash water was 7. The powder obtained was finally dried in a vacuum drying cabinet at 80° C. and 10 -2 This was dried at bar overnight, giving 19.5 g of a black solid.

[0125] Inventive Example 4: Treatment of porous carbon particles with NaOH solution at room temperature (without washing) 20 g of carbon from Comparative Example 1 was charged into a 250 ml flask and mixed with a NaOH solution (0.4424 g NaOH in 50 ml distilled water) at room temperature. The suspension was then stirred at room temperature for 1 hour and then filtered through a suction filter. The powder obtained was finally dried at 80° C. and 10° C. in a vacuum drying cabinet. -2 This was dried at bar overnight, giving 19.5 g of a black solid.

[0126] Inventive Example 5: Treatment of porous carbon particles with 1M LiOH at room temperature A 250 ml flask was charged with 20 g of carbon from Comparative Example 1 and mixed with 160 ml of 1M LiOH (aq) at room temperature. The suspension was then heated to 100° C. and boiled under reflux for 3 hours. After cooling to ambient temperature, the suspension was filtered through a suction filter and the solid product was washed with distilled water until the pH of the wash water was 7. The powder obtained was finally dried in a vacuum drying cabinet at 80° C. and 10 -2 The mixture was dried at 400 bar overnight, yielding 19.6 g of a black solid.

[0127] Inventive Example 6: Treatment of porous carbon particles with 1M KOH at room temperature A 250 ml flask was charged with 20 g of carbon from Comparative Example 1 and mixed with 160 ml of 1 M KOH (aq.) at room temperature. The suspension was then heated to 100° C. and boiled under reflux for 3 hours. After cooling to ambient temperature, the suspension was filtered through a suction filter and the solid product was washed with distilled water until the pH of the wash water was 7. The powder obtained was finally dried in a vacuum drying cabinet at 80° C. and 10 -2 The mixture was dried at 400 bar overnight, yielding 19.6 g of a black solid.

[0128] The physical properties of the porous carbon particles are summarized in Table 1 below.

[0129] [Table 1]

[0130] Production of silicon-carbon composite particles Comparative Example 1A: Silicon-carbon composite particles from the porous carbon particles of Comparative Example 1 In a tubular reactor, the porous carbon particles of Comparative Example 1 (specific surface area = 2140 m) were placed in a fused silica boat. 2 / g, Gurvich pore volume = 1.01 cm 3 The reactor was charged with 3.0 g of 1,2-dichloroethane (1.0 g / g, pH=5.4). After inerting the reactor with nitrogen, the reactor was heated to 410° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 4.9 hours. The reactor was then flushed with inert gas, cooled to room temperature, and the product was removed.

[0131] Comparative Example 1B: Silicon-carbon composite particles from the porous carbon particles of Comparative Example 1 at reduced temperatures The porous carbon of Comparative Example 1 (specific surface area = 2140 m) was placed in a fused silica boat in a tubular reactor. 2 / g, Gurvich pore volume = 1.01 cm 3The reactor was charged with 3.0 g of 1,2-dichloroethane (10% SiH4 in N2, 10 L(STP) / h). After inerting the reactor with nitrogen, the reactor was heated to 380° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 10.2 hours. The reactor was then flushed with inert gas, cooled to room temperature, and the product was removed.

[0132] Example 1A: Silicon-carbon composite particles from the porous carbon particles of Example 1 In a tubular reactor, the porous carbon particles of Example 1 (specific surface area = 2010 m) were added to a fused silica boat. 2 / g, Gurvich pore volume = 0.95 cm 3 The reactor was charged with 3.0 g of 1,2-dichloroethane (10% SiH4 in N2, pH=10.7). After inerting the reactor with nitrogen, the reactor was heated to 380° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 4.6 hours. The reactor was then flushed with inert gas, cooled to room temperature, and the product was removed.

[0133] Example 2A: Silicon-carbon composite particles from the porous carbon particles of Example 2 In a tubular reactor, the porous carbon particles of Example 2 (specific surface area = 1980 m) were added to a fused silica boat. 2 / g, Gurvich pore volume = 0.98 cm 3 The reactor was charged with 3.0 g of 1,2-dichloroethane (1.0 g / g, pH=9.0). After inerting the reactor with nitrogen, the reactor was heated to 380° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 8.5 hours. The reactor was then flushed with inert gas, cooled to room temperature and the product was removed.

[0134] Example 3A: Silicon-carbon composite particles from the porous carbon particles of Example 3 In a tubular reactor, the porous carbon particles of Example 3 (specific surface area = 1940 m) were added to a fused silica boat. 2 / g, Gurvich pore volume = 0.96 cm 3The reactor was charged with 3.0 g of 1,2-dichloroethane (10% SiH4 in N2, pH=10.7). After inerting the reactor with nitrogen, the reactor was heated to 380° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 5.4 hours. The reactor was then flushed with inert gas, cooled to room temperature, and the product was removed.

[0135] Example 4A: Silicon-carbon composite particles from the porous carbon particles of Example 4 In a tubular reactor, the porous carbon particles of Example 4 (specific surface area = 1900 m) were added to a fused silica boat. 2 / g, Gurvich pore volume = 0.94 cm 3 The reactor was charged with 3.0 g of 1,2-dichloroethane (10% SiH4 in N2, 10 L(STP) / h). After inerting the reactor with nitrogen, the reactor was heated to 380° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 5.7 hours. The reactor was then flushed with inert gas, cooled to room temperature, and the product was removed.

[0136] Inventive Example 5A: Silicon-carbon composite particles from the porous carbon particles of Inventive Example 5 In a tubular reactor, the porous carbon particles of Example 5 (specific surface area = 2030 m) were added to a fused silica boat. 2 / g, Gurvich pore volume = 0.95 cm 3 The reactor was charged with 3.0 g of 1,2-dichloroethane (10% SiH4 in N2, 10 L(STP) / h). After inerting the reactor with nitrogen, the reactor was heated to 380° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 7.1 hours. The reactor was then flushed with inert gas, cooled to room temperature, and the product was removed.

[0137] Example 6A: Silicon-carbon composite particles from the porous carbon particles of Example 6 In a tubular reactor, the porous carbon particles of Example 6 (specific surface area = 1990 m) were added to a fused silica boat. 2 / g, Gurvich pore volume = 0.93 cm 3The reactor was charged with 3.0 g of 1,2-dichloroethane (10% SiH4 in N2, 10 L(STP) / h). After inerting the reactor with nitrogen, the reactor was heated to 380° C. When the reaction temperature was reached, reaction gas (10% SiH4 in N2, 10 L(STP) / h) was passed through the reactor for 8.0 hours. The reactor was then flushed with inert gas, cooled to room temperature, and the product was removed.

[0138] Inventive Example 7A: Silicon-carbon composite particles from the porous carbon particles of Inventive Example 1 by reaction in a pressure reactor The reaction was carried out in an electrically heated autoclave with a volume of 594 ml, consisting of a cylindrical lower part (beaker) and a lid with several connections (e.g. for gas supply, gas removal, temperature and pressure measurement). The stirrer used was a helical stirrer with a very narrow clearance. The height of this stirrer corresponds to about 50% of the clear height inside the reactor. The helical stirrer was constructed in such a way that it allowed a direct temperature measurement in the bed. The autoclave was filled with the porous carbon of invention example 1 (specific surface area = 2010 m2). 2 / g, Gurvich pore volume = 0.95 cm 3 The autoclave was first evacuated. Then, SiH4 (15.6 g) was injected at a pressure of 15.1 bar. The autoclave was then heated to a temperature of 425°C over 90 minutes and held at that temperature for 240 minutes. During the course of the reaction, the pressure rose to 76 bar. Over a period of 12 hours, the autoclave was cooled to room temperature (21°C). After cooling, the pressure in the autoclave was 35 bar. The pressure in the autoclave was reduced to 1 bar and then the autoclave was flushed 5 times with nitrogen, 5 times with lean air with an oxygen fraction of 5%, 5 times with lean air with an oxygen fraction of 10%, and then 5 times with air. 21.3 g of silicon-carbon composite particles were isolated in the form of a fine black solid.

[0139] The reaction conditions for producing the silicon-carbon composite particles and the physical properties of the particles are summarized in Table 2 below.

[0140] [Table 2]

[0141] The data for the production of silicon-carbon composite particles of the present invention clearly show that advantageously, infiltration of silicon occurs much faster when employing the method of the present invention to produce porous carbon particles having an alkali metal concentration >0.05 wt% and a pH above 7.5.

[0142] Evaluation of silicon-carbon composite particles in electrochemical cells Inventive Example 8: Anodes containing the inventive silicon-carbon composite particles of Inventive Example 1A and electrochemical testing in lithium ion batteries 29.71 g of polyacrylic acid (dried to constant weight at 85°C; Sigma-Aldrich, Mw ~ 450,000 g / mol) and 756.60 g of deionized water were stirred for 2.5 hours on a shaker (290 1 / min) until the polyacrylic acid was completely dissolved. Lithium hydroxide monohydrate (Sigma-Aldrich) was added to the solution in portions until the pH was 7.0 (measured using a WTW pH 340i pH meter and SenTix RJD probe). The solution was then mixed on a shaker for another 4 hours. 3.87 g of the neutralized polyacrylic acid solution and 0.96 g of graphite (Imerys, KS6L C) were introduced into a 50 ml vessel and mixed with a planetary mixer (SpeedMixer, DAC 150 SP) at 2000 rpm. Next, 3.40 g of the silicon-carbon composite particles of the present invention of Inventive Example 1A were added and stirred at 2000 rpm for 1 minute. Next, 1.21 g of 8% conductive carbon black dispersion and 0.8 g of deionized water were added and kneaded on a planetary mixer at 2000 rpm. The mixture was then dispersed in a dissolver at 3000 rpm and a constant temperature of 20° C. for 30 minutes. The ink was then degassed again in a planetary mixer at 2500 rpm under reduced pressure for 5 minutes.

[0143] The finished dispersion was then coated onto a 0.03 mm thick copper foil (Schlenk Metallfolien, SE-Cu58) using a film stretching frame (Erichsen, model 360) with a gap height of 0.1 mm. The anode coating thus produced was then dried for 60 min at 60 °C and 1 bar air pressure. The average weight per unit area of ​​the dried anode coating was 2.2 mg / cm. 2 and the coating density is 0.8 g / cm 3 It was.

[0144] The electrochemical studies were carried out in a two-electrode button cell (type CR2032, Hohsen). The electrode coating was used as the counter or negative electrode (Dm = 15 mm) and had a content of 94.0% and an average weight per unit area of ​​15.9 mg / cm. 2 A coating based on lithium nickel manganese cobalt oxide 6:2:2 (supplied by SEI) was used as the working or positive electrode (Dm=15 mm). A glass fiber filter paper (Whatman, GD Type D) soaked with 60 μl of electrolyte served as the separator (Dm=16 mm). The electrolyte used consisted of a 1.0 molar solution of lithium hexafluorophosphate in a 1:4 (v / v) mixture of fluoroethylene carbonate and diethyl carbonate. The cell was assembled in a glove box (<1 ppm H2O, O2). The moisture content in the dry mass of all components used was less than 20 ppm.

[0145] Electrochemical testing was performed at 22°C. The cells were charged by cc / cv (constant current / constant voltage) method with a constant current of 15 mA / g (corresponding to C / 10) for the first cycle, 75 mA / g (corresponding to C / 2) for the subsequent cycles, and constant voltage after reaching a voltage limit of 4.2 V until the current was less than 1.5 mA / g (corresponding to C / 100) or less than 3 mA / g (corresponding to C / 50). The cells were discharged by cc (constant current) method with a constant current of 15 mA / g (corresponding to C / 10) for the first cycle, and 75 mA / g (corresponding to C / 2) for the subsequent cycles until the voltage limit of 2.5 V was reached. The specific current chosen was based on the weight of the coating on the positive electrode. The electrodes were selected to have a cathode:anode capacity ratio of 1:1.2.

[0146] Inventive Example 9: Anodes containing the inventive silicon-carbon composite particles of Inventive Example 5A and electrochemical testing in lithium ion batteries The silicon-containing material of the present invention of Inventive Example 5A was used to prepare an anode as described in Inventive Example 8. The anode was incorporated into a lithium ion battery as described in Inventive Example 8 and subjected to the same testing procedures.

[0147] Example 10: Anodes containing the silicon-carbon composite particles of the present invention of Example 6A and electrochemical testing in lithium ion batteries The silicon-containing material of the present invention of Inventive Example 6A was used to prepare an anode as described in Inventive Example 8. The anode was incorporated into a lithium ion battery as described in Inventive Example 8 and subjected to the same testing procedures.

[0148] Comparative Example 11: Anode containing silicon-carbon composite particles of the present invention of Inventive Example 6A and electrochemical testing in a lithium ion battery The non-inventive silicon-containing material of Comparative Example 1A was used to fabricate an anode as described in Inventive Example 8. The anode was incorporated into a lithium ion cell as described in Inventive Example 8 and subjected to the same testing procedures.

[0149] The results of the electrochemical evaluation are summarized in Table 3 below.

[0150] [Table 3]

[0151] It is clear that by using the silicon-carbon composite particles of the present invention, a cycle stability significantly higher than that achieved by using conventional silicon-carbon composite particles can be achieved.

Claims

1. a) an alkali metal or alkaline earth metal concentration of 0.05 to 0.86 wt %; and b) pH > 7.5 The silicon-carbon composite particles have the following structure:

2. 10. A method for producing silicon-carbon composite particles according to claim 1 by infiltration of silicon from a silicon precursor selected from liquid or gaseous silicon precursors at 20° C. and 1013 mbar in the presence of porous carbon particles, the porous carbon particles being from treatment with a basic alkali metal or alkaline earth metal compound in a molar ratio of 100:1 to 5:1 based on the carbon present in the porous carbon particles, having an alkali metal or alkaline earth metal concentration of 0.1 to 2.03 wt %, and a pH > 7.

5.

3. Diameter percentile d 50 2. The silicon-carbon composite particles of claim 1, having a volume weighted particle size distribution of from 0.5 to 20 μm.

4. 4. The silicon-carbon composite particle of claim 1 or 3 having at least 30 wt. % silicon obtained by infiltration with silicon.

5. 5. The silicon-carbon composite particle of claim 1, 3 or 4, wherein the silicon is present in the pores and on the outer surface of the silicon-carbon composite particle in the form of a layer or layers formed from silicon particles having a thickness of 1 μm or less.

6. 100m 2 The silicon-carbon composite particles according to any one of claims 1 or 3 to 5, having a BET specific surface area of ​​0.1 to 0.5 μm / g or less.

7. 7. The silicon-carbon composite particle of claim 4, wherein the pore volume P is at least 100 vol.% relative to the volume of silicon provided by infiltration of silicon in the silicon-carbon composite particle, and the pore volume P of the silicon-carbon composite particle is obtained from the sum of the gas-accessible pore volume and the gas-inaccessible pore volume.

8. 3. The method according to claim 2, wherein the silicon infiltration is carried out in a reactor selected from a fluidized bed reactor, a horizontal to vertical rotary tube furnace, an open or closed fixed bed reactor, and a pressure reactor.

9. 9. The method according to claim 2 or 8, wherein the infiltration with silicon is carried out at 280 to 900°C.

10. 10. The method of claim 2, 8 or 9, wherein the silicon-carbon composite particles of any one of claims 1 or 3 to 7 are produced by infiltration of silicon from a silane selected from monosilanes and chlorine-containing silanes.

11. An anode material for a lithium ion battery comprising the silicon-carbon composite particles according to any one of claims 1 or 3 to 7.

12. 12. An anode comprising a current collector coated with the anode material of claim 11.

13. A lithium ion battery comprising at least one anode comprising the silicon-carbon composite particles of any one of claims 1 or 3-7.

Citation Information

Patent Citations

  • Method for preparing porous carbon and white carbon black by using diatomite

    CN101913595A

  • Preparation method of Si-C composite negative electrode material of lithium ion battery

    CN103000902A

  • Silicon-carbon composite material and preparation method thereof, and lithium ion battery

    CN103346303A

  • Method for preparing silicon carbide / porous carbon composite material with high specific surface area

    CN103706407A

  • A silicon-coated carbon particle composite material, its preparation method and equipment, and its applications.

    CN105185970B